Recording secrets for the small studio - Senior, Mike (Abingdon ; New York : Routledge, 2022)
"In this new edition, discover how to achieve commercial-grade recordings, even in the smallest studios, by applying power-user techniques from the world's most successful producers. Recording Secrets for the Small Studio is based on the backroom strategies of more than 250 famous names. This thorough and down-to-earth guide leads you through a logical sequence of practical tasks to build your live-room skills progressively from the ground up, with user-friendly explanations which introduce technical concepts on a strictly need-to-know basis. On the way, you'll unravel the mysteries of many specialist studio tactics and gain the confidence to tackle a full range of real-world recording situations. Specifically designed for small-studio enthusiasts, this book provides an intensive training course for those who want a fast track to releasing quality results. While the chapter summaries, assignments, and extensive online resources are perfect for school and college use. Learn the fundamental principles of mic technique that you can apply in any recording scenario -- and how to avoid those rookie mistakes that all too often compromise the sonics of lower-budget productions. Explore advanced techniques which help industry insiders maintain their competitive edge even under the most adverse conditions: creative phase manipulation, improvised acoustics tweaks, inventive monitoring workarounds, subtle psychological tricks... Find out where you don't need to spend money, as well as how to make a limited budget really count. Make the best use of limited equipment and session time, especially in situations where you're engineering and producing single-handed. Pick up tricks and tips from celebrated engineers and producers across the stylistic spectrum, including Steve Albini, Neal Avron, Roy Thomas Baker, Joe Barresi, Howard Benson, Tchad Blake, T-Bone Burnett, Joe Chiccarelli, Jack Douglas, Gus Dudgeon, Geoff Emerick, Brian Eno, Paul Epworth, Shawn Everett, Humberto Gatica, Nigel Godrich, Imogen Heap, Ross Hogarth, Trevor Horn, Rodney Jerkins, Glyn Johns, Leslie Ann Jones, Eddie Kramer, Jacquire King, Daniel Lanois, Sylvia Massy, Alan Meyerson, Justin Niebank, Hugh Padgham, Gary Paczosa, Tony Platt, Jack Joseph Puig, David Reitzas, Bob Rock, Rafa Sardina, Jim Scott, Laura Sisk, Fraser T Smith, Randy Staub, Bruce Swedien, Butch Vig, Tony Visconti, Butch Walker, Matt Wallace, Young Guru, and many, many more... Now extensively expanded and updated, with new sections on contact mics, software instruments, squash mics, and ensemble depth distortion"--
Keywords: Popular music -- Production and direction; Sound studios; MUSIC / Recording & Reproduction; TECHNOLOGY / Acoustics & Sound